Two large deletions extending beyond either end of the RHD gene and their red cell phenotypes. Issue 1 (January 2018) - Srivastava, Kshitij; Stiles, David; Wagner, Franz; Flegel, Willy
Abstract Only two partial deletions longer than 655 nucleotides had been reported for theRHD gene, constrained within the gene and causing DEL phenotypes. Using a combination of quantitative PCR and long-range PCR, we examined three distinct deletions affecting parts of theRHD gene in three blood donors. TheirRHD nucleotide sequences and exact boundaries of the breakpoint regions were determined. DEL phenotypes were caused by a novel 18.4 kb deletion and a previously published 5.4 kb deletion of theRHD gene; a D-negative phenotype was caused by a novel 7.6 kb deletion. Examination of the deletion-flanking regions suggested microhomology-mediated end-joining, replication slippage, and non-homologous end-joining, respectively, as the most likely mechanisms for the three distinct deletions. We described two new deletions affecting parts of theRHD gene, much longer than any previously reported partial deletion: one was the first deletion observed at the 5′ end of theRHD gene extending into the intergenic region, and the other the second deletion observed at its 3′ end. Large deletions present at either end are a mechanism for a much reduced RhD protein expression or its complete loss. Exact molecular characterization of such deletions is instrumental for accurateRHD genotyping.